Sucessão em uma pastagem tropical abandonada : mudanças estruturais e estimativa de recuperação florestal. - Zviejkovski, Iuli Pessanha (2008)
During the 70's the territorial occupation and colonisation of the region of the upper Paraná river floodplain promoted the degradation of local ecosystems with the implement of the culture of coffee. Such culture was replaced afterwards with extensive cattle raising. Given the framework of environmental destruction and the importance of floodplain, it was established in 1997 the Field of Island and Várzeas Paraná river Environmental Protection - (APA-IVRP) in order to protect the last remaining stretch of Paraná river in Brazilian territory free from dams. With the creation of APA there was withdrawal of cattle from the islands and abandonment of pastures, which started up a process of secondary succession. To determine the pattern of succession of abandoned areas in the region, it was compared the vegetation floristic structural characteristics in three different areas: a pasture with 10 years of abandonment (Forest 1); a 55 year-old forest formed on a bar of coalescence (forest 2), and a fragment of remaining forest (forest R), in Puerto Rico island, PR, Brazil. The forest survey was conducted through a phytosociological study in two layers: canopy and subcanopy. The results showed that the basal area and total density, as well as the number of species was greater for the forest R. Analyzing the layers separately, the subcanopy of forests 1 and 2 showed signs of speed recovery, the values of diversity and richness similar to the values of the forest R, but the composition of species was different. So that forest one can reach values of basal area similar to remaining forest, the process is slow and can take up to 124 years. The exotic species were some of the most abundant species in the forests 1 and 2, featuring the disturbance suffered by cattle raising. Given the results, can be said that the creation of APA-IVRP was an important contribution to reducing the rate of environmental degradation in the area, encouraging the natural processes of recovery from it. However, measures of control and prevention of exotic species are necessary aimed at speeding up the restoration of the area.